The Beginnings of Ecology in the Bible - Najda, Andrzej Jacek (Studia Ecologiae et Bioethicae, 2004)
The development of ecology in contemporary times leads to the question: what are the beginnings of this branch of science? The Bible proposes the answer to us in the first story of creation. Man receives as his task the dominion over the world (Gen 1,26b) and its subduing (Gen 1,28). Ecology is thus the fulfillment of the creating will of God.